2011
DOI: 10.1038/nature10441
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of dynamin

Abstract: Dynamin-related proteins (DRPs) are multi-domain GTPases that function via oligomerization and GTP-dependent conformational changes to play central roles in regulating membrane structure across phylogenetic kingdoms. How DRPs harness self-assembly and GTP-dependent conformational changes to remodel membranes is not understood. Here we present the crystal structure of an assembly-deficient mammalian endocytic DRP, dynamin 1, lacking the proline-rich domain, in its nucleotide-free state. The dynamin 1 monomer is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
318
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 246 publications
(328 citation statements)
references
References 42 publications
10
318
0
Order By: Relevance
“…Comparison of the dynamin tetramer with the filament-like arrangements observed in the crystal structures of dynamin 1 2,3 shows that the tetramer is bent, such that the angle between the outer stalks is changed by 20° (Fig. 1, 4a).…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…Comparison of the dynamin tetramer with the filament-like arrangements observed in the crystal structures of dynamin 1 2,3 shows that the tetramer is bent, such that the angle between the outer stalks is changed by 20° (Fig. 1, 4a).…”
mentioning
confidence: 95%
“…3b), but not at the outer, non-assembled sides of the tetramer. Previous studies have shown that mutation of R399 in loop L2 S completely destroys higher-order assembly and dynamin function 2,3,11 . In our structure, R399 of an outer molecule forms salt bridges to E410 in α2 S and to E345 in L1N S in the outer and inner molecules of the opposite dimer, respectively.…”
mentioning
confidence: 98%
See 3 more Smart Citations